Saccadic eye movements are able to reduce body sway in mildly-affected people with Multiple Sclerosis - Santinelli, Felipe Balistieri [UNESP]; van Emmerik, Richard E.A.; Silva, Fabiana Araújo [UNESP]; Imaizumi, Luis Felipe Itikawa [UNESP]; Penedo, Tiago [UNESP]; Canzonieri, Ana Maria; Rodrigues, Sérgio Tosi [UNESP]; Zago, Paula Favaro Polastri [UNESP]; Barbieri, Fabio Augusto [UNESP] (Elsevier, 2019)
Background: Multiple Sclerosis (MS) is a neurodegenerative and inflammatory disease that impacts both visual and postural control. It is currently unknown how the integration between visual and postural control is affected in people with MS (PwMS). It has been shown in healthy individuals that saccadic eye movements can decrease body sway as result as the integration of eye and postural movements. Objective: Investigate the effect of saccadic eye movement on postural control in PwMS and compare with neurologically healthy people. Methods: Thirteen mildly affected PwMS (1.53 ± 1.03 on Expanded Disability Status Scale - EDSS) and 12 healthy neurologically people participated in this study. Postural control was assessed on a force platform under two eye movement conditions: fixation on a central target and saccadic eye movement. The dependent variables assessed were the displacement, velocity, root-mean-square (RMS) and area of postural center of pressure and the number, duration, variability, fixations errors and eye response time. A mobile eye tracker was used to record eye movement. Two-way ANOVA (group and eye movement) for postural variables was performed. For the eye variables, one-way ANOVA with factor to group was performed. The p-value was maintained at 0.05 for all statistical analysis and the effect sizes were based on Cohen's d. Results: No group or interaction effects (group*eye movement) were found for postural and eye variables. However, the saccadic eye movement attenuated the postural displacement in anteroposterior (AP) direction (p < 0.001, Cohen's d = 4.677), RMS AP (p < 0.001, Cohen's d = 4.399) and area (p < 0.013, Cohen's d = 2.163) in comparison with the central fixation condition in both groups. The Cohen's d showed a large effect between groups for fixation errors (d = 0.741). Conclusion: Both groups presented similar postural control performance in both eye movement conditions. Moreover, PwMS could attenuate body sway similarly to the control group, showing that the central integration of dynamic eye movements and postural control is preserved in mildly affected PwMS.
Keywords: Human movement; Multiple Sclerosis; Postural control; Saccadic eye movement